Was Not the Woman Created in the Likeness of God? Pauline Midrashic Reading of Gen 1–3 in 1 Cor 11:7–12 - Matand Bulembat , Jean-Bosco (The Biblical Annals, 2022)
To demonstrate his claim in 1 Cor 11:2–16 about how a Christian man and woman should wear their hair during liturgical worship, Paul uses several types of arguments, including Scripture (vv. 7–12). In v. 7, he states that “A man should not cover his head, because he is the image and glory of God, but a woman is the glory of man” (NAB). Most readers today, question the soundness of such an argument and may accuse Paul of misogyny. Does he not, contrary to what Gen 1:26–27 asserts, contend that the woman was not created in the image of God? The present study argues that Paul’s position can be better understood only if one, on the one hand, highlights the points of his argumentation and, on the other hand, considers the techniques of the Jewish theory of interpretation of the Scriptures in practice at the time of the Apostle. Paul is doing a Midrashic reading of Gen 1–3 narratives about the creation of human beings to assert the importance of both man and woman to behavior during Christian liturgical worship in such manner that they respect their specific dignities. At the end, Paul seems to be more “philogynist” than people use to appreciate.